T.O.B.A. Time : Black Vaudeville and the Theater Owners' Booking Association in Jazz-Age America - Scott, Michelle R., 1974- (Book collections on Project MUSE., 2023)
"Black vaudevillians and entertainers joked that T.O.B.A. stood for "tough on black artists." But the Theater Owner's Booking Association (T.O.B.A.) played a foundational role in the African American entertainment industry and provided a training ground for icons like Cab Calloway, Bessie Smith, Ethel Waters, Sammy Davis Jr., the Nicholas Brothers, Count Basie, and Butterbeans and Susie. Michelle R. Scott's institutional history details T.O.B.A.'s origins and practices while telling the little-known stories of the managers, producers, performers, and audience members involved in the circuit. Looking at the organization over its eleven-year existence (1920-1931), Scott places T.O.B.A. against the backdrop of what entrepreneurship and business development meant in black America at the time. Scott also highlights how intellectuals debated the social, economic, and political significance of black entertainment from the early 1900s through T.O.B.A.'s decline during the Great Depression.Clear-eyed and comprehensive, T.O.B.A. Time is a fascinating account of black entertainment and black business during a formative era"--